Leitura em voz alta: programa de intervenção fonoaudiológica para estudantes de graduação em produção audiovisual - Oliveira, Gabriela Carolina de (2013)
Introduction: The speech therapy by the expressiveness has grown in fields, such as radio and television. Due to this progress, the speech therapist has faced some obstacles. One of them is the hardness of working with the interpretation of text read aloud, since many cannot comprehend what they read. Objective: To analyze the performance of graduating students on audiovisual production, during the process of speech therapy focusing on reading aloud. Method: The intervention was performed in 6 weekly meetings, lasting 1 and a half hour each one of them with four groups of volunteers. They answered a reader profile questionnaire. Recordings were made from two different new segments of pre and post intervention contents. At the end of each meeting, the researcher recorded and registered the contents on a daily basis. Results: The sample profile showed that 61.53% were male and the average age was 25.61 years, 84.61% of the persons considered themselves readers, but highlighted the purpose of reading solely for learning ( 69.23%) and a minor percentage, referred to it as a pleasurable activity (30.76%). Regarding the recordings made, 88.46% were considered an appropriate post intervention; aspects of prosody (emphasis, pauses, inflection and speed) were extensively highlighted by the use of post intervention, which contributed to the production of meaning and interpretation of the message. Throughout the analysis of the intervention process, persons have discovered experiences, strategies and exercises that changed the understanding and the interpretation as well when read aloud. Conclusion: The Speech Therapy program focusing on oral reading was positive, as improved text understanding and provided a more appropriate reading aloud